CORAL LARVAL DISPERSAL MODEL ON CONSERVATION AREA OF KAPOPOSANG MARINE TOURISM PARK - Zulfikar Afandy; Ario Damar; Syamsul Bahri Agus; Budy Wiryawan (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2017)
The availability of information related to the pattern of connectivity between coral reef is one of the key in coral reef conservation management. The identification of pattern of connectivity in the form of dispersion dynamics of coral larvae is very important as the development of coral reef itself is highly depended upon the external input, which this input must be accordingly managed in order to support the continuity of coral larvae supply. This research’s objectives are including to create the coral larvae dispersal model of Marine Protected Area (MPA) of Kapoposang. For instance, the modelling of coral larvae dispersal had been conducted using the biophysics modelling which combined the biological and physics factor in order to obtain the recruitment scenario and the traces of larvae dispersal. This simulation used coral larvae object with the Pelagic Larval Duration (PLD) for 30 days, the larvae release was conducted during the full moon and during the west and east monsoon. The result of the larvae dispersion model has indicated that the coral larvae dispersion process was influenced by the currents and variation of monsoons. Based coral connectivity pattern on Kapoposang found site Gondongbali, Kapoposang2, Suranti and Pamanggangang as a source. Then other location as sink by received larvae from other site are Gondongbali, Kapoposang, Pamanggangang, Taka Karangkarangang, Taka Pallawangang and Taka Palekko. Keywords connectivity, coral reef, larva dispersal, marine protected area, twp kapoposang